Get the answers you need at Westonci.ca, where our expert community is always ready to help with accurate information. Connect with a community of experts ready to help you find solutions to your questions quickly and accurately. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.
Sagot :
To determine which equation could represent the function [tex]\( f \)[/tex] with zeros at [tex]\( -1 \)[/tex] and [tex]\( -5 \)[/tex], we need to understand that the zeros of a function are the values of [tex]\( x \)[/tex] that make the function equal to zero.
Given the zeros [tex]\( -1 \)[/tex] and [tex]\( -5 \)[/tex]:
1. The zero [tex]\( x = -1 \)[/tex] implies that one of the factors of the function is [tex]\( (x + 1) \)[/tex].
2. The zero [tex]\( x = -5 \)[/tex] implies that the other factor of the function is [tex]\( (x + 5) \)[/tex].
Thus, the function [tex]\( f(x) \)[/tex] can be written as the product of these factors:
[tex]\[ f(x) = (x + 1)(x + 5) \][/tex]
Let's confirm this form matches our given options:
1. [tex]\( f(x) = (x - 1)(x + 5) \)[/tex]
2. [tex]\( f(x) = (x + 1)(x - 5) \)[/tex]
3. [tex]\( f(x) = (x + 1)(x + 5) \)[/tex]
4. [tex]\( f(x) = (x - 1)(x - 5) \)[/tex]
Among these, the equation [tex]\( f(x) = (x + 1)(x + 5) \)[/tex] matches our required factors. Hence, the correct answer is:
[tex]\[ f(x) = (x + 1)(x + 5) \][/tex]
Given the zeros [tex]\( -1 \)[/tex] and [tex]\( -5 \)[/tex]:
1. The zero [tex]\( x = -1 \)[/tex] implies that one of the factors of the function is [tex]\( (x + 1) \)[/tex].
2. The zero [tex]\( x = -5 \)[/tex] implies that the other factor of the function is [tex]\( (x + 5) \)[/tex].
Thus, the function [tex]\( f(x) \)[/tex] can be written as the product of these factors:
[tex]\[ f(x) = (x + 1)(x + 5) \][/tex]
Let's confirm this form matches our given options:
1. [tex]\( f(x) = (x - 1)(x + 5) \)[/tex]
2. [tex]\( f(x) = (x + 1)(x - 5) \)[/tex]
3. [tex]\( f(x) = (x + 1)(x + 5) \)[/tex]
4. [tex]\( f(x) = (x - 1)(x - 5) \)[/tex]
Among these, the equation [tex]\( f(x) = (x + 1)(x + 5) \)[/tex] matches our required factors. Hence, the correct answer is:
[tex]\[ f(x) = (x + 1)(x + 5) \][/tex]
We appreciate your time. Please come back anytime for the latest information and answers to your questions. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.